BUILDING HIGHER EDUCATION COMPETITIVE ADVANTAGE THROUGH JOB SATISFACTION, OPTIMIZING LOYALTY AND WORK ABILITY OF OPERATIONAL EMPLOYEES - Sutris Sutris; Nurani Puspa Ningrum; Tuti’ Nadhifah (Nurul Jadid University, 2025)
This study analyzes the influence of job satisfaction, loyalty, and work ability on employee performance at Muhammadiyah University of Kudus. The results show a positive influence between job satisfaction on employee performance at Muhammadiyah University of Kudus, this can be seen from the tvalue of 4.601 > ttable of 1.664 with a significance level below 5%. There is a positive influence between loyalty on employee performance at Muhammadiyah University of Kudus, this can be seen from the tvalue of 4.601 > ttable of 1.664 with a significance level below 5%. There is a positive influence between work ability on employee performance at Muhammadiyah University of Kudus, this can be seen from the tvalue of 4.601 > ttable of 1.664 with a significance level below 5%. And there is an influence of job satisfaction, loyalty, and work ability on employee performance at Muhammadiyah University of Kudus, which is proven to be significant, the Fvalue of 25.869 > Ftable of 3.91 with a significance level below 5%